2015
DOI: 10.4103/2229-3485.148802
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review to evaluate and characterize the health economics and outcomes research studies in India

Abstract: Aim:This systematic literature review was conducted to identify, evaluate, and characterize the variety, quality, and intent of the health economics and outcomes research studies being conducted in India.Materials and Methods:Studies published in English language between 1999 and 2012 were retrieved from Embase and PubMed databases using relevant search strategies. Two researchers independently reviewed the studies as per Cochrane methodology; information on the type of research and the outcomes were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Since no standardisation exists for the interpretation of QHES scores, the score 75–100 was set as good, the score 51–74 as fair, the score 25–49 as poor and the score 0–24 as extremely poor. 13–15 …”
Section: Quality Assessmentmentioning
confidence: 99%
“…Since no standardisation exists for the interpretation of QHES scores, the score 75–100 was set as good, the score 51–74 as fair, the score 25–49 as poor and the score 0–24 as extremely poor. 13–15 …”
Section: Quality Assessmentmentioning
confidence: 99%
“…Moreover, the review included both full economic evaluations (cost per outcome description with comparison of alternatives) as well as simple cost analyses. Another systematic review from India by Mishra et al found 132 articles published between 1999 and 2012 [10]. However, this was not focussed on full economic evaluations alone, and included several other studies such as cost-only analysis and studies which measured changes in outcome (estimation of quality of life) alone.…”
Section: Introductionmentioning
confidence: 96%
“…Devoting one percent of the country's GDP to a well-designed health program nationwide could save as many as 480 million healthy years of life [2]. Mishra and Nair conducted a systematic literature review of 132 cost effectiveness, cost analyses, and burden of illness research studies of health programs in India [16]. The survey found that there is a need for better assessment of healthcare resources in India.…”
Section: About Cost Effectivenessmentioning
confidence: 99%